COMPARISON OF THE EFFICACY OF MAGNESIUM SULPHATE AND DIAZEPAM IN THE CONTROL OF TETANUS SPASM - Ali, Gauhar; Kamal, Mustafa; Khan, Abdul Naseer (Journal of Postgraduate Medical Institute, 2011)
Objective: To compare the efficacy of magnesium sulphate and diazepam in controlling the tetanus spasm. Methodology: This randomized clinical trial was conducted in Intensive Care Unit, Lady Reading Hospital, Peshawar from April 2009 to October 2010. Thirty six patients were included in study after fulfilling inclusion criteria. They were divided into 2 groups equally. Group I included patients that received intravenous diazepam, while Group II patients received intravenous magnesium sulphate for the control of spasm. Outcome variables included cessation of spasm, uncontrollable spasm, death, stay in Intensive Care Unit, need for artificial ventilation and complications. These were analyzed and the comparison was done in both groups to see the outcome of patients. Results: Male to Female ratio was 5:1. Mean stay (in days) in Intensive Care Unit was 30 6 for Group I, while 14.2+ 3 for Group II. Outcome was better in Group II as compared to Group I with p-value <0.01, except for the cessation of spasm and death which were almost equal in both groups. Eighteen patients needed ventilatory support in Group I, while 4 patients needed ventilatory support in Group II. The length of stay was double in Group I as compared to Group II. Only one patient had developed Magnesium toxicity, which was successfully managed, while 8 patients developed complications from Diazepam. Conclusion: Magnesium sulphate was found superior in terms of reducing severity of spasm and minimizing stay of patients in Intensive Care Unit as compared to diazepam.